Time for Science-Based National Targets for Environmental Sustainability: An Assessment of Existing Metrics and the ESGAP Framework - Usubiaga-Liaño, Arkaitz; Ekins, Paul (Frontiers in Environmental Science, 2021)
Despite the overwhelming scientific evidence on the ongoing degradation of the environment, there is a clear gap between the urgency of the environmental crisis and the policy measures put in place to tackle it. Because of the role of metrics in environmental governance, the way environmental information is translated into metrics is of utmost relevance. In this context, we propose criteria to assesses the suitability of environmental metrics to monitor environmental sustainability at the national level. After assessing well-known environmental metrics such as the Sustainable Development Goal indicators and the Environmental Performance Index, we conclude that countries still lack robust and resonant metrics to report on progress towards environmental sustainability. In order to bridge this metric gap, we present the environmental sustainability gap (ESGAP) framework, which builds on the concepts of strong sustainability, critical natural capital, environmental functions and science-based targets. Different composite indicators are proposed as part of the ESGAP framework. Through these metrics, the framework has the potential to embed strong sustainability thinking and science-based targets in nations in which these concepts are not currently sufficiently reflected in policies.